Populism and Mass Clientelistic Politics in Classical Athens - Hedetoft, Christopher H. (Classica et Mediaevalia, 2022)
The potential dangers and uses of populism are as never before at the forefront of discourse on modern democracy. From political scientists to the media, politicians and of course the public, everyone seems to have an opinion in the heated debate about the role of populism in politics. In most cases, contemporary populists are chastised by pundits and academics for undermining democracy and dividing the nation. Yet perhaps we need a new, albeit historical, perspective. Was populism present in a democratic state outside of our own time frame – and if so, how did it work? Using a number of works on populism as a theoretical framework, most importantly Jan-Werner Müller’s What is populism? (2016), this paper seeks to uncover, analyze and discuss popu- lism, rhetoric, leadership and power relations in the direct democracy of classical Athens (508-323 BCE). Through an in-depth study of Aristophanes’ comedy Knights, Thucydides’ history of the Peloponnesian War, and various forensic orations, I conclude that populism was very much alive and well in ancient Athens, and likely even embedded in the politico-legal structure of their society. Furthermore, I find that the relationship between elite orators and the masses of the Athenian citizenry was primarily an interde- pendent and mutually reciprocal one.